La mortalidad materna en Ecuador: un caso de estudio económico durante el periodo 1985-2019 - Soto Aguirre., Andrea Isabel (2023)
Maternal mortality is a social and economic problem. In Ecuador about 18 women die each month from pregnancy-related causes. The maternal mortality rate has been increasing to reach 70% in the country. Therefore, the objective of this research is to analyze maternal mortality through an economic study during the period 1985-2019 in Ecuador. In this way, a time series methodology was used in which an ARDL model was estimated, in addition to the data sources available from the World Bank, Penn World Table, World Inequality Ecuador and Data Futures Platform. According to the results obtained with the model, there is a relationship between maternal mortality and socioeconomic factors; however, there are long-term effects with the variables household expenditure, employment and human development index. The recommendations put forward in this work focus on strengthening public health services, especially in rural areas, by investing in adequate control of the pregnancy process, improving the quality of education, employing policies to support women who live in a state of vulnerability, and campaigns to inform new mothers about the pregnancy process.